Carbonate chemistry dynamics in shellfish farming areas along the Chilean coast: natural ranges and biological implications - Saavedra, Luisa M; Saldías, Gonzalo S; Broitman, Bernardo R; Vargas, Cristian A (ICES Journal of Marine Science, 2020)
Abstract The increasing shellfish aquaculture requires knowledge about nearshore environmental variability to manage sustainably and create climate change adaptation strategies. We used data from mooring time series and in situ sampling to characterize oceanographic and carbonate system variability in three bivalve aquaculture areas located along a latitudinal gradient off the Humboldt Current System. Our results showed pHT <8 in most coastal sites and occasionally below 7.5 during austral spring–summer in the lower (−30°S) and central (−37°S) latitudes, related to upwelling. Farmed mussels were exposed to undersaturated (Ωarag < 1) and hypoxic (<2 ml l−1) waters during warm seasons at −37°S, while in the higher latitude (43°S) undersaturated waters were only detected during colder seasons, associated with freshwater runoff. We suggest that both Argopecten purpuratus farmed at −30°S and Mytilus chilensis farmed at −43°S may enhance their growth during summer due to higher temperatures, lower pCO2, and oversaturated waters. In contrast, Mytilus galloprovincialis farmed at 37°S grows better during spring–summer, following higher temperatures and high pCO2. This knowledge is relevant for aquaculture, but it must be improved using high-resolution time series and in situ experimentation with farmed species to aid their adaptation to climate change and ocean acidification.